PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 PADA PT. XYZ - Putri Aisyah Adawiyah; Lovinta Happy Atrinawati (Universitas Teknokrat Indonesia, 2020)
PT. XYZ is a company that serves fabrication and inspection services. PT. XYZ serves companies in Indonesia, both companies engaged in mining, palm oil processing factories, construction, and shipping. Information technology governance is needed to align the company's business objectives with its technology's performance. This research is encouraged by the absence of an assessment of information technology governance. This research intended to help the company knew the important processes in the company. This research uses the COBIT 2019 framework that is the latest version of COBIT released by ISACA. This company's analysis uses 11 design factors that are supported by a toolkit. The results are information technology governance values and their important processes. The results of this research are information technology governance design of the company and knew the important processes to PT. XYZ. These important processes include APO06 Managed budget and costs, APO09 Managed service agreements, APO12 Managed risk, BAI04 Managed availability and capacity, and BAI11 Managed projects with target capability levels 3 and 4.